Correlations of Serum Magnesium and Potassium in Acute Myocardial Infarction, Chronic Ischemic Heart Disease and Normal Healthy Volunteers of Bangladesh - Choudhury, MBK; Hossain, MM; Akhtaruzzaman, M; Uddin, MM Jamal; Rahman, MS; Islam, MS; Jinnah, CMK; Hoque, N (Bangladesh Journal of Medical Biochemistry, 2013)
Magnesium (Mg) and potassium (K) are the major intracellular cations whose presence in the serum are low, but minor changes of those may show a remarkable change in the various body functions specially in the heart. The study was designed to find out the correlation between serum Mg and K in acute myocardial infarction (AMI), chronic ischemic heart disease (CIHD) and normal healthy volunteers. It was carried out over a period of 18 months in the Department of Biochemistry, Bangabandhu Sheikh Mujib Medical University (BSMMU) in collaboration with Department of Cardiology, Sir Salimullah Medical College & Mitford Hospital (SSMC & MH) and Atomic Energy Center, Dhaka. A total of 101 subjects were included in which 32 subjects were AMI, 34 CIHD and 35 normal healthy volunteers. Serum glucose and serum creatinine were estimated to exclude diabetes and renal dystrophies. Estimation of serum CK-MB and ECG tracing were done as diagnostic tools of AMI and to categories the subjects into various groups. Serum Mg was estimated by Atomic absorption spectrophotometer and serum K by Ion sensitive electrode. The present study shows that there is a strong positive correlation of serum Mg and K in AMI, CIHD and healthy control subjects (r = 0.566, p<0.01 level). So it is suggested to estimate and supplement both Mg and K in IHD patients for their better management. DOI: http://dx.doi.org/10.3329/bjmb.v3i2.13812 Bangladesh J Med Biochem 2010; 3(2): 50-56